The Factors that Drives the Cost Management Efficiency of Oil and Gas companies in Emerging Markets: The Case of Eurasian Economic Union - Yespergenova , Lyazzat; Dosmanbetova, Aliya; Baisheva , Yengilik; Zhakipbekov , Dinmukhamed; Zhumabayeva, Myrzabike; Faizulayev, Alimshan (International Journal of Energy Economics and Policy, 2023)
The main aim of this empirical work is to investigate cost management efficiency determinants of oil and gas companies in Eurasian Economic Union. The data was carefully gathered with updated financial data of 24,813 firm-year observations for the following period 2012-2020. Two main models were developed: with social responsibility and without social responsibility. In order to conduct panel data regression analysis, we employ two-step system GMM. The Durbin, Wu-Hausman test was used to find endogeneity, before we use the system GMM. Findings reveal that capital structure, taxes, and the oil demand crisis of 2014-2015 to be the most dominant determinants of cost management efficiency in the studied sample of oil and gas companies. Results suggest that increased taxes boost the cost management efficiency of oil and gas firms. Findings of the present study offer many insights and policy implications to help investors, managers, and policy makers. The contribution to the literature is twofold.